Biocompatibility and Bioactive Potential of New Calcium Silicate-based Endodontic Sealers: Bio-C Sealer and Sealer Plus BC - Alves Silva, Evelin Carine [UNESP]; Tanomaru-Filho, Mario [UNESP]; Silva, Guilherme Ferreira da; Delfino, Mateus Machado [UNESP]; Cerri, Paulo Sergio [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP] (Elsevier B.V., 2020)
Introduction: Bio-C Sealer (BC; Angelus, Londrina, PR, Brazil) and Sealer Plus BC (SPBC; MK Life, Porto Alegre, Brazil) are new ready-to-use bioceramic endodontic sealers. The aim of this study was to evaluate the biocompatibility and bioactive potential of BC and SPBC sealers in comparison with AH Plus (AHP; Dentsply DeTrey Gmbh, Konstanz, Germany) in subcutaneous tissue of rats. Methods: Polyethylene tubes filled with materials and empty tubes, serving as the control group, were implanted in the subcutaneous tissues of rats. After 7, 15, 30, and 60 days, the tubes with connective tissue were removed, and inflammatory cells (ICs)/mm(2) and immunolabeled cells for interleukin (IL)-6 were evaluated. Osteocalcin and von Kossa analysis were also performed. Data were submitted to analysis of variance and Tukey tests, with a significance level of 5%. Results: At 7 days, SPBC showed lower ICs than BC (P < .05). AHP exhibited greater immunolabeled cells for IL-6 (P < .05). After 15 days, BC showed lower ICs and IL-6 compared with other materials. At 30 days, SPBC and AHP showed higher values for ICs (P < .05). After 60 days, calcium silicate sealers did not show statistical difference (P > .05) for ICs and IL-6, with values lower than AHP (P < .05). The materials showed positive structures to von Kossa staining. BC exhibited osteocalcin labeling in all periods. SPBC showed osteocalcin labeling from 15-60 days. AHP and the control group did not exhibit osteocalcin labeling. Conclusions: BC and SPBC sealers are biocompatible and present bioactive potential.
Keywords: Biocompatibility; calcium silicate; endodontics; root canal filling material